Practical and theoretical aspects of geological interpretation of gravitational, magnetic and electric fields : proceedings of the 45th Uspensky International Geophysical Seminar, Kazan, Russia /: proceedings of the 45th Uspensky International Geophysical Seminar, Kazan, Russia. (2019) - Unknown
No abstract available